Pengembangan Media Pembelajaran Interaktif Menggunakan Articulate Storyline Pada Materi Atmosfer Untuk Peserta Didik SMP - Nadiatul Hafidah; Yudha Irhasyuarna; Mella Mutika Sari (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
The research objective of developing an articulated storyline media based on atmosphere material is to explain how interactive and valid learning media work. The ADDIE development model is combined with the R&D method in this study. Validation was carried out using assessment sheets by material experts and also the media as a data collection technique for this research, and using tests and questionnaires for students. Based on the results of the research that has been done, this learning media gets a score of 94.56% from material experts and also the media. It can be concluded that this finding is an Articulate Storyline medium for atmosphere material that is very effective in learning natural sciences in seventh grade junior high school.